CB574 – Manual towards a clumsy city: Runner-up - Granoux, Romain; Justet, Francois; Minier, Margaux (4D Journal of Landscape Architecture and Garden Art, 2013)
The design of an adaptable and consequently sustainable project requires to accept and to produce the vulnerability of urban space and its functions, with the aim of facing the unforeseen and apprehending its mutations. The vulnerable indicates what is threatened and perishable. Our strength is to make vulnerability a criterion of sustainability
Keywords: competition